Adaptive Windowing for OFDM with Dense Subcarrier Spacing in Mobile Channels - Robert, Jörg; Zöllner, Jan; Slimani, Mariem (OFDM 2012, 17th International OFDM Workshop 2012 (InOWo'12); Proceedings of, 2012)
This paper presents an algorithm for adaptive windowing for OFDM with dense subcarrier spacing. Instead of using a rectangular DFFT window a shaped window is employed. This algorithm has been implemented in our software-based DVB-T2 receiver. The receiver consciously adapts the shaping window in order to reach the best compromise between Inter Symbol and Inter Carrier Interference in highly mobile channels. The results indicate that a significant robustness increase can be obtained. Keywords ?? DVB-T2, OFDM windowing, software-defined radio.
Keywords: Channel estimation; Digital video broadcasting; Estimation; Mobile communication; Noise measurement; OFDM; Receivers